The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3906/tar-1405-60
|View full text |Cite
|
Sign up to set email alerts
|

The performance of Melolontha grubs on the roots of various plant species

Abstract: Melolontha grubs are polyphagous and are adapted to feeding on plants of varying nutritional value. Our research sought to investigate whether host plant quality affects first-instar grub development, weight gain, or mortality. Ten plant taxa of the families Polygonaceae, Brassicaceae, Asteraceae, Fabaceae, and Pinaceae were tested. The quality of each plant species was estimated based on the root content of phenols, condensed tannins, soluble sugars, starch, nitrogen, and carbon. Retarded development, high mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
(36 reference statements)
0
29
0
Order By: Relevance
“…officinale is often attacked by larvae of M . melolontha (Coleoptera, Scarabaeidae; Huber, Bont, et al, ), a highly polyphagous root feeder (Hauss & Schütte, ; Sukovata, Jaworski, Karolewski, & Kolk, ). Previous work found that the interaction between T .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…officinale is often attacked by larvae of M . melolontha (Coleoptera, Scarabaeidae; Huber, Bont, et al, ), a highly polyphagous root feeder (Hauss & Schütte, ; Sukovata, Jaworski, Karolewski, & Kolk, ). Previous work found that the interaction between T .…”
Section: Introductionmentioning
confidence: 99%
“…and its interaction with the common cockchafer Melolontha melolontha. In grasslands across Europe, T. officinale is often attacked by larvae of M. melolontha (Coleoptera, Scarabaeidae; Huber, Bont, et al, 2016), a highly polyphagous root feeder (Hauss & Schütte, 1976;Sukovata, Jaworski, Karolewski, & Kolk, 2015). Previous work found that the interaction between T. officinale and M. melolontha is modulated by the presence of sympatric plant species (Huang, Zwimpfer, Hervé, Bont, & Erb, 2018).…”
mentioning
confidence: 99%
“…A serious problem in Poland are also soil pests, especially grubs, including larvae of the widely widespread herbivorous May bug (Melolontha melolontha L.), a beetle from the Scarabaeidae family (Milenkovic and Stanisavljevic 2003;Totic 2014;Skrzecz et al 2014;Sukovata et al 2015). Other insects affecting raspberry crops are the raspberry beetle (Byturus tomentosus De Geer), the twospotted spider mite (Tetranychus urticae Koch), and the blossom weevil (Anthonomus rubi Herbst).…”
Section: Raspberry Pests and Diseasesmentioning
confidence: 99%
“…Together, these results suggest that T.481 repens becomes resistant to M. melolontha because of low digestibility associated with high 23 the fact that T. officinale roots re nutrient rich. In an interspecific study,Sukovata et al (2015) 486 showed that M. melolontha larvae grow better on plants that are more sugar-rich. Although 487 latex defenses protect T. officinale to a certain degree by prompting larvae to move to congeners 488 with lower latex defense levels(Bont et al, 2017;Huber et al, 2016), this form of resistance is 489 not sufficient for T. officinale to avoid attack by M. melolontha in the field.…”
mentioning
confidence: 99%